ALGEBRAIC CONSTRUCTION OF THE POLYNOMIAL BASIS OF A SIX-NODE OCTAHEDRON - Motailo, Anjelika; Khomchenko, Anatoliy (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents second-degree polynomial bases for the finite element in the form of an octahedron constructed by means of matrix calculus. The obtained functions are harmonics according to Laplace. Geometric properties of the corresponding level surfaces are analyzed.